Effect of various plant starches on the quality characteristics of starch-based sweetened cow milk yoghurt (Journal of the Bangladesh Agricultural University, 2016)
In this study, the textural, rheological and colour properties of different starch-based sweetened cow milk yoghurt were analyzed. Stickiness increased with increased addition level of modified starch for both homogenized (-2.231 to -5.304 N) and unhomogenized (-1.505 to -4.834 N) yoghurt sample. Firmness increased linearly for unhomogenized cow milk yoghurt sample at different incorporation level (3.019 to 4.887 N) but the homogenized cow milk yoghurt samples did not shown any clear significant difference. Viscosity also increased with increased addition level of modified starch and unhomogenized yoghurt sample at different incorporation level of modified starch showed clear and significant difference from sample to sample. Firmness, stickiness and viscosity of potato starch-based cow milk yoghurt with homogenization did not show any significant difference, but unhomogenized yoghurt sample showed linear increase of viscosity and firmness that ranged from 0.213 to 0.525 Pa.s and from 2.669 to 4.014 N, respectively. Stickiness of unhomogenized sample also increased with increased potato starch incorporation level. Viscosity increased with increased corn starch incorporation for homogenized sample. The pH values were more or less similar and the colour values showed it was lightness as white for all cases. The highest incorporation level (2%) was found for corn starch followed by potato (1.5%) and modified (1.0%) starch.J. Bangladesh Agril. Univ. 14(1): 119-126, June 2016